Female Body in Cordillera Music Videos - Bea de Alyssa B. Castro; Miel Ysabel P. Sanculi (Department of Communications, Universitas Islam Indonesia, 2017)
Music has always been a significant part of life. This is probably the reason why humanity has invented and innovated ways of how music could always be present wherever and whenever it wants to be heard.In the Philippines one of the most underrated music genres is the country music produced in the local regions. One of the regions that produce this kind of music is the Cordillera Administrative Region which is also one of the most dominated regions during the American colonization period in the Philippines. It is located at the northern part of Luzon, and is known as the home of the Igorots, or the “people from the mountains”.Due to the colonial influence, the CAR, including the local songs and music videos produced in this region were seen as highly influenced by the American cowboy culture. The production and consumption of this music and these music videos are representations of the Cordilleran or Igorot’s representation and portrayal of the way they view their culture, society, and selves.The main focus of this research is the way the Igorot perceive the female body. The music videos were analyzed through their lyrics, mise-en-scene, the roles given to women, and the interrelation of these three elements within the representation process. Through the lens of Laura Mulvey’s Male Gaze Theory, it was seen that the portrayal of female body in the music videos was objectified by both voyeuristic and fetishistic gaze. This study also claims that the ideologies of the people working behind the production of the music videos affect the domestication of women in the Cordillera. Keywords: female body, indigenous people, male gaze